Study of Smart Campus Development Using Internet of Things Technology - Marti Widya Sari; Prahenusa Wahyu Ciptadi; R. Hafid Hardyanto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
This paper describes the development of smart campus using Internet of Things (IoT) technology. Through smart campus, it is possible that a campus is connected via online by the outside entity, so that the teaching approach based on technology can be conducted in real time. This research was conducted in smart education, smart parking and smart room. Observation and literature studies were applied as the research method with the related theme for the sake of system design of smart campus. The result of this research is the design of smart campus system that includes smart education development, smart parking and smart room with the sake of Universitas PGRI Yogyakarta as the case study.